Letramento digital: os gêneros textuais digitais nas práticas de leitura e escrita nos anos iniciais do ensino fundamental - Guerra, Melissa Andrade (Brasil, 2023)
This research with a qualitative approach aimed to analyze the contribution of digital textual genres to reading and writing practices in the fifth year of elementary school in a public school in the city of Parintins-AM and is based on studies by Bakhtin (1997); Soares (2002; 2004; 2009, 2017); Kleiman (2005); Marcuschi (2005); Rojo and Moura (2012); Martins and Botelho (2020) and documents such as the National Common Curricular Base (2018) and the Amazonian Curricular Reference (2019). The field research was carried out in a fifth grade elementary school class and the data collection instruments were participant observations and the application of a questionnaire to students and teachers. The results show that digital technologies provide new learning environments and access to digital and multimodal textual genres, important resources in the development of students' reading, speaking and writing skills. Teachers emphasize the use of information and communication technologies to expand language practices in different areas of knowledge in the early years of elementary school, however, there are factors that prevent digital inclusion and expansion of digital literacy in the school context, such as: lack of digital technological resources, lack of internet access and continuous training of teachers. Therefore, it is necessary to invest in public policies for digital inclusion at school and, consequently, to expand digital literacy and thus intensify reading and writing practices, considering digital textual genres, in order to contribute to the development of language skills and abilities of the students.